r(x) = 3x^{2} + 5 |
s(x) = 2x - 1 |

r'(x) = 6x | s'(x) = 2 |

r(x) = 6x - 11 | s(x) = 8x + 1 |

r'(x) = 6 | s'(x) = 8 |

r(x) = (5x - 2)(2x + 3) | s(x) = x - 4 |

Use the product rule table
below to get: r'(x) = 20x + 11 |
s'(x) = 1 |

r(x) = 5x - 2 | s(x) = 2x + 3 |

r'(x) = 5 | s'(x) = 2 |

v(x) = 8x + 3 | f(v) = v^{2} |

v'(x) = 8 | f'(v) = 2v
or 2(8x + 3) |

v(x) = 8 - 5x | f(v) = v^{1/2} |

v'(x) = -5 | f '(x) = v^{-1/2}/2
or (8 - 5x) |

r(x) = -6x | s(x) = (7x - 1)^{2} |

r'(x) = -6 | s'(x) = 14(7x - 1) |

r(x) = -6 | s(x) = e^{x+1} |

r'(x) = 0 | s'(x) = e^{x+1} |

g(x) = 5x^{2} - 3x |
g'(x) = 10x - 3 |

r(x) = 5x^{2} |
s(x) = e^{x} |

r'(x) = 10x | s'(x) = e^{x} |